2022
DOI: 10.1155/2022/4834791
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Downregulated Exosome-Associated Gene ENPP1 as a Novel Lipid Metabolism and Immune-Associated Biomarker for Hepatocellular Carcinoma

Abstract: Exosome plays an important role in the occurrence and development of tumors, such as hepatocellular carcinoma (LIHC). However, the functions and mechanisms of exosome-associated molecules in LIHC are still underexplored. Here, we investigated the role of the exosome-related gene ENPP1 in LIHC. Comprehensive bioinformatics from multiple databases revealed that ENPP1 was significantly downregulated in LIHC tissues. The patients with downregulated ENPP1 displayed a poor prognosis. Immunohistochemistry (IHC) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…sEV CD147 could suppress FAO by suppressing p38 MAPK signaling to down-regulate the expressions of PPARα and its target genes of CPT1A and ACOX1, which consequently reprogrammed cancer cell lipid metabolism except for its functions in de novo lipogenesis [ 36 ]. Ectonu nucleotide pyrophosphatase/phosphodiesterase 1(ENPP1) is a type II transmembrane glycoprotein, a decrease in which is connected with poor prognosis in HCC patients [ 44 , 45 ]. Down-regulated sEV-associated ENPP1 and FA fatty acid degradation and PPAR signaling pathways are the signaling pathways for the enrichment of sEV ENPP1 co-expression molecules [ 46 ].…”
Section: Sevs Are Involved In the Metabolic Reprogramming Of Cancer C...mentioning
confidence: 99%
See 1 more Smart Citation
“…sEV CD147 could suppress FAO by suppressing p38 MAPK signaling to down-regulate the expressions of PPARα and its target genes of CPT1A and ACOX1, which consequently reprogrammed cancer cell lipid metabolism except for its functions in de novo lipogenesis [ 36 ]. Ectonu nucleotide pyrophosphatase/phosphodiesterase 1(ENPP1) is a type II transmembrane glycoprotein, a decrease in which is connected with poor prognosis in HCC patients [ 44 , 45 ]. Down-regulated sEV-associated ENPP1 and FA fatty acid degradation and PPAR signaling pathways are the signaling pathways for the enrichment of sEV ENPP1 co-expression molecules [ 46 ].…”
Section: Sevs Are Involved In the Metabolic Reprogramming Of Cancer C...mentioning
confidence: 99%
“…Down-regulated sEV-associated ENPP1 and FA fatty acid degradation and PPAR signaling pathways are the signaling pathways for the enrichment of sEV ENPP1 co-expression molecules [ 46 ]. Additionally, ENPP1 may take part in the supervision of other lipid metabolic routes, including FA ω-oxidation [ 45 ]. The above studies confirmed that sEVs reprogram cancer metabolism in the anabolism and catabolism of lipids through their cargos, thus promoting the occurrence and development of tumors.…”
Section: Sevs Are Involved In the Metabolic Reprogramming Of Cancer C...mentioning
confidence: 99%